PENCIPTAAN BUKU FOTOGRAFI LANDSCAPE WISATA ALAM KABUPATEN JOMBANG SEBAGAI UPAYA BRAND AWARENESS KEPADA REMAJA - Darussalam, Darussalam; Bahruddin, Muh; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2015)
Abstract: Many things are done by a region to promote tourism destinations, one of which is nature in Jombang district, in addition to a district that is still relatively young, the potential of nature tourism in Jombang many interesting and should be developed. Tourism in Jombang district is still lacking in the promotion process, especially in nature, as evidenced by the lack of recognition of Jombang society itself will be natural tourism potential, because Jombang still less famous with its religious tour. Nature in Jombang district need to be considered, because the actual natural scenery in Jombang not inferior to nature in other cities, nature in Jombang need for recognition because there are still many who do not know the existence of destinations attractive tourist district Jombang.Jombang district turned out to have some interesting natural attractions, some of the natural attractions in the region Jombang district obtained the data from http://jombangkab.go.id among others such as Tretes waterfall, Goa Sigolo-Golo, and Kedung Cinet. With the creation of landscape photography book Jombang nature, it is expected the development of nature tourism in Jombang district is growing and getting ahead in the future, because this book other than as reverensi and knowledge of nature in Jombang as well as tourist guide books are very interesting to read.Â Keywords: Handbook, natural beauty, adventure, Jombang district, Tourism Potential.